EP295 Investigating the effect of hypercapnia, hypoxia and pH on cellular proliferation in cervical cancer. (1st November 2019) - Gentles, L; Sharma Saha, S; Case, M; Korompelis, P; Drew, Y; Curtin, N; O'Donnell, RL
Abstract : Introduction/Background: In the phase III LACC cervical cancer trial, shorter disease-free survival and overall survival was observed in patients treated with minimally invasive radical hysterectomy in comparison to traditional open surgery. One hypothesis for this difference is an adverse effect of the prolonged exposure to the hypoxic, CO2 -rich, acidotic environment created during minimally invasive surgery. Greater cervical tumour hypoxia-inducible factor 1α (HIF-1α) indicating tissue hypoxia has previously been shown to be a strong independent prognostic marker in early stage cervical cancer. This pre-clinical study aimed to evaluate the effect of hypercapnia, hypoxia and pH on cervical cancer cell growth. Methodology: Three cervical cancer cell lines (Hela, SiHa, C33ca) were incubated in variable CO2 (5–20%) and O2 (5%–20%) conditions, in an InvivO2 incubator with HEPES medium for 3 doubling times, standardised for humidity and temperature. Growth rates were assessed by Sulforhodamine B colorimetric (SRB) assays with measurement of pH in spent media. Matched controls were incubated in routine physiological conditions. Results: There was a 1.5-fold difference in doubling time of cell lines under physiological conditions with doubling times ranging from 22 to 34 hours. Incubation in a hypercapnic environment persistently resulted in growth inhibition across all three cell lines at all seeding densities, with mean growth inhibition of 45.0% (SD 16.0%) at 20% CO2 . Inhibition of growth was greatest in C33a, the most rapidly dividing cell line with mean reduction in growth of 55.5%. pH remained within physiological range falling by a mean of 0.45 to a minimum of 7.12. Conclusion: Hypercapnia results in growth inhibition in cervical cancer cell lines, independent of acidosis. It is unlikely that exposure to the CO2 rich intra-operative environment during minimally invasive surgery is responsible for the poor prognosis reported in the LACC trial. Disclosure: Nothing to disclose.